2018
DOI: 10.21307/acee-2018-007
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Fiberly Reinforced Concrete Using Polypropylene Fibre with Virgin and Recycled Road Aggregate

Abstract: A b s t r a c t This research work mainly focuses on improving the concrete strength based on fiber reinforcement both in compression and tension. Concrete with various mix proportions containing dosage of Polypropylene (PP) fiber of lengths ranging from 13 to 25 mm with coarse aggregate replacement levels at 10%, 20%, and 30% by dismantled road aggregate were made and the compressive and tensile strengths were investigated. The experimental test results revealed high compressive and tensile strength at curing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…Similarly, for each mixture and for the three above curing periods, 15 cylinders having diameter of 150 mm and height of 300 mm were cast to check the spilt tensile strength of concrete. The specimens were fabricated and removed from moulds after 24 hours and kept in a totally wet environment for 7, 14 and 28 days curing period[22] [23][24] [25].…”
mentioning
confidence: 99%
“…Similarly, for each mixture and for the three above curing periods, 15 cylinders having diameter of 150 mm and height of 300 mm were cast to check the spilt tensile strength of concrete. The specimens were fabricated and removed from moulds after 24 hours and kept in a totally wet environment for 7, 14 and 28 days curing period[22] [23][24] [25].…”
mentioning
confidence: 99%
“…It became obvious that 1% fiber reinforcement ratio was the optimal percentage in this study to enhance the mechanical properties of concrete. The 1% fiber reinforcement ratio threshold was also observed by [22] [23]. In general, concrete is inherently weak in tension, and to enhance the tensile strength fibers contribute at significant degree.…”
Section: Observationsmentioning
confidence: 63%
“…2). They reported that the decrease in strength was due to the unavailability of the required amount of calcium hydroxide [44][45][46]. Sethy et al [18] made concrete which containing (5%, 10%, 15% and 20%) red mud as substitute of cement.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…There was a 2.5% to 5% improvement in compressive strength for each percentage replacement. Beyond 20% replacement with red mud the strength decreased [46][47][48][49].…”
Section: Compressive Strengthmentioning
confidence: 99%